Case study analyzing political and policy issues surrounding Massachusetts Ballot Question Number 1 (Tufts Archival Research Center, 2007)
Case study analyzing political and policy issues surrounding Massachusetts Ballot Question Number 1, which establishes and additional excise tax on tobacco. Traces origins of ballot question. Explores coalitions on either side of the issue. Discusses conclusion of vote and anticipated consequences.